The effects of caffeine on migrain headache: a literature review - Coutinho, Isadora Pinheiro; Nunes, Melyssa Maria Fernandes da Rocha; Filho, Otavio Pereira da Silva; Lousada, Lívio Martins; Pinheiro, Giulia Rebouças; Soares, Ana Clara Mendes; Azevedo, Marina Pinheiro Uchoa; Moura, Lucas Eliel Beserra (Headache Medicine, 2023)
Full abstract in PDF.